Perkembangan Dan Kesenjangan Riset Literasi Fisik Di Asia: Sebuah Scoping Review - Naufal Nur Fadhillah Karim; Natalia Irandah; Heldi Kurniadi; Arya Darajat; Carsiwan . (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
Physical inactivity has become a global public health crisis, with approximately 1.8 billion adults worldwide failing to meet recommended levels of physical activity. Asia records the highest prevalence, ranging from 45% to 48%. Physical literacy (PL) has emerged as a holistic framework to address this challenge; however, a comprehensive mapping of PL research across Asian contexts remains limited. This study aims to examine the development, research gaps, and emerging trends in PL research in Asia using a bibliometric-based scoping review approach. Methods A bibliometric analysis was conducted on 1,142 documents indexed in the Scopus database from 2010 to 2026. The analysis employed R-Bibliometrix and VOSviewer to map publication productivity, international collaboration patterns, topic evolution, and conceptual networks within the field. Results: The number of publications increased substantially, from 7 articles in 2010 to 322 articles in 2025, with a notable surge after 2019. China emerged as the dominant contributor with 1,009 publications. Indonesia also demonstrated considerable productivity (223 articles) but had the lowest citation impact, with an average of two citations per article. International research collaboration remained relatively limited, accounting for only 26.18% of publications. Research themes evolved from a predominantly methodological focus during 2010–2016 to an emphasis on health literacy and health promotion between 2020 and 2025. The predominance of cross-sectional study designs (128 publications) highlights a shortage of intervention-based and longitudinal research. Conclusion PL research in Asia is currently in a phase of rapid expansion, supported by strong growth momentum. Nevertheless, further progress requires enhanced international collaboration, the development of culturally appropriate measurement instruments, and more evidence-based intervention and longitudinal studies to effectively inform public health policy